Tool for the Meaningful Consideration of Language Barriers in Qualitative Health Research. (January 2020) - Premji, Stephanie; Kosny, Agnieszka; Yanar, Basak; Begum, Momtaz
Individuals who experience language barriers are largely excluded as participants from health research, resulting in gaps in knowledge that have implications for the development of equitable policies, tools, and strategies. Drawing on the existing literature and on their collective experience conducting occupational health research in contexts of language barriers, the authors propose a tool to assist qualitative researchers and representatives from funding agencies and ethics review boards with the meaningful consideration of language barriers in research. There remain gaps and debates with respect to the relevant ethical and methodological guidance set forth by funding agencies and institutions and proposed in the scientific literature. This article adds to knowledge in this area by contributing our experiences, observations, and recommendations, including around the issue of conducting research in contexts of more or less linguistic diversity.